If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 5 * 3 = 11 Multiply 5 * 3 2x + 15 = 11 Reorder the terms: 15 + 2x = 11 Solving 15 + 2x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 2x = 11 + -15 Combine like terms: 15 + -15 = 0 0 + 2x = 11 + -15 2x = 11 + -15 Combine like terms: 11 + -15 = -4 2x = -4 Divide each side by '2'. x = -2 Simplifying x = -2
| 2ln(2*x+1)-3ln(x+1)+ln(x+1)=0 | | 3x+18=3x+34 | | 2(4-5x)=7-5(x-2) | | 20+1d=30+.5d | | 4n+3m=11 | | -30=5w+5 | | 64=9u-u | | 103+5x=63 | | 2(x)=54 | | x/-6=120 | | 2y+16=48 | | 2x-2-3=21-34x | | 31+4x=86 | | xln(x)-1=0 | | -54-8x=2x | | (1.09^x)/50 | | 4/5/5/4= | | v=1/3*b*h | | 7n-3n=3n+15 | | 3-12x+18=33 | | 9x-10y=24 | | -4-8=4(-3n+2) | | 9x-11=3x+8 | | 4x(3-y)=0 | | x+5(x-2)=8 | | 24+3x=3x(7-1) | | 9n+1=10 | | 10x=2+5 | | X-0.2x=520 | | 6x+29=-25 | | f(x)=x-(3/lnx) | | f(x)=x-3/lnx |